A black shale protolith for gold-tellurium mineralisation in the Dalradian Supergroup (Neoproterozoic) of Britain and Ireland. (2nd October 2017) - Parnell, J.; Perez, M.; Armstrong, J.; Bullock, L.; Feldmann, J.; Boyce, A. J.
ABSTRACT: The Dalradian Supergroup of Britain and Ireland is mineralised by gold-tellurium vein deposits. The host succession includes carbonaceous, pyritic shales (pelites) which were a source of trace elements, including gold and tellurium. LA-ICP-MS mapping of pyrite crystals shows that late stages are enriched in gold, tellurium and lead, representing concentration of these elements during metamorphism and related hydrothermal activity. The sulphur isotope composition of the pyrite varies with stratigraphic position, reflecting an origin for the pyrite in the depositional environment through microbial sulphate reduction. Where pyrite was converted to pyrrhotite, trace element contents are much lower, indicating element liberation during metamorphism. These observations are consistent with a model of black shale protoliths for orogenic gold deposits.